Mitogenome Phylogenetics of Spiruromorpha Porpoise Parasite: Insights Into Phylogeny of Crassicauda magna - Lei Han; Yuling Yang; Maolin Lu; Hongyan Yu; Yaxian Lu; Mengchao Zhou; Tianlu Liu; Ruisi Zhang; Bingyao Chen; Zhijun Hou (Pathogens)
(1) Background: Crassicauda magna is a major parasite of large porpoises and whales and has been classified in the Habronematoidea family. However, there has been a great controversy regarding its classification. Mitochondria have an important function in revealing taxonomic and evolutionary history. (2) Methods: In this study, we sequenced the mitochondrial genome of C. magna and conducted a phylogenetic analysis with the mitochondrial sequences of species belonging to the Habronematoidea family. (3) Results: The complete mitochondrial genome was 13,604 bp and it has an AT-rich sequence and one non-coding region (NCR). The reconstruction of the ancestral state showed that the gene orders of all species in Spirurina were conserved. The phylogenetic tree indicates that C. magna is closer to Heliconema longissimum (Physalopteroidea) than Tetrameres grusi (Habronematoidea). (4) Conclusions: This study provides new evidence that C. magna is phylogenetically closer to Physalopteroidea at the molecular taxonomic level.